2020
DOI: 10.1080/15623599.2020.1734417
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for international construction joint ventures adoption: a systematic literature review

Abstract: Recognizing that there exist discrete sets of factors driving the adoption of international construction joint ventures (ICJVs) for different countries, organizations, and stakeholders, this study aims to identify the drivers and integrate them into a classification framework for better understanding. The Virtual Libraries (VL) of respective journals were accessed directly to retrieve the related papers for the study. Popular search engines such as Google Scholar, the Web of Science, and Engineering Village we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 93 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…The mean values were estimated by summing up the frequencies of the constructs divided by the number constructs grouped into that category. This method was adopted by Chan et al (2020) for categorization in a review study. The identified constructs were grouped into components that depict a similar phenomenon in the various articles reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean values were estimated by summing up the frequencies of the constructs divided by the number constructs grouped into that category. This method was adopted by Chan et al (2020) for categorization in a review study. The identified constructs were grouped into components that depict a similar phenomenon in the various articles reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…The focus group involved four other academics who are well vested in PPP. Chan et al (2020) applied this method and efficiently categorised drivers for the adoption of international construction joint ventures. Six categories were developed from the 40 win–win constructs identified and are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…This prompts PPP operations to be coordinated within well-networked organizational structures, managerial and institutional strategies that are directed towards the achievement of universally determined service delivery outcomes. In fact, the co-production and co-regulation initiatives advanced by the new public governance approach enable public service stakeholders to exchange information among themselves to have better PPP inventions of solving intricate society problems (Chan et al, 2020).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Contextually, there exists some varying importance of factors driving ICJVs adoption as Chan et al (2020) argued. Previous studies have identified different drivers for implementing ICJVs, yet they shed little empirical investigation on the relative importance of these drivers between developed and developing countries/jurisdictions and focused on very few driving factors.…”
Section: Icjvs: Global Insights For Sustainable Growthmentioning
confidence: 99%